MEMBANGUN KESADARAN EKOLOGIS; INTERVENSI YAYASAN HAkA DALAM MENJAGA KAWASAN EKOSISTEM LEUSER ACEH - Nainda, Namya; Ilham, Iromi; Chalid, Ibrahim (FISIP Universitas Malikussaleh, 2024)
So far, the community of Sumber Makmur, Tenggulun District, Aceh Tamiang Regency, has depended on oil palm as their primary source of income. This condition impacts land clearing activities to expand planting areas, some of which are included in the leuser ecosystem area. Of course, this is a threat to ecological sustainability. Therefore, the HAkA Foundation took the initiative to educate the community through empowerment programmes so that the intervention could change the community's perspective on ecology positively. This study discusses the transformation process carried out by the HAkA Foundation and the socio-cultural implications that occurred in the Sumber Makmur community after the entry of the NGO. This research uses a qualitative approach with data collection techniques of observation, in-depth interviews, and document studies. The results showed that the existence and interventions carried out by the HAkA Foundation in Sumber Makmur Village were able to create positive changes and change the perspective of the surrounding community in protecting the leuser ecosystem area. The ecological citizenship programme impacts environmental awareness, so the community maintains, protects, and preserves the Leuser Ecosystem Area. The skills training programme on utilising palm oil waste opens up opportunities for economic improvement for the community, including by producing palm oil stick plates. In addition, skills training also leads to traditional food processing that can be marketed to increase income for the community.